Fuzzy decision making in Business intelligence in the context of Gilgit-Baltistan - Rehman, Shams Ur; Shaheen, Nusrat; Haider, Fakhar; Khan, M. Salim (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
The main purpose of this paper is to investigate and implement fuzzy decision based on unequal objectives and minimization of regret for the decision making in the business intelligence and to compare the weight of products while the minimization of regret that uses regression of products in Gilgit-Baltistan. Here we will convert the verbal expressions in to linguistic variables and use in fuzzy decision making model, which influences the main two factors, one is effect of the influence on the product and second its payoff for the most effectiveness on the products.